Comparison of cosmetic results after treatment in women with breast cancer who received additional radiation to the tumor bed - I. A. Akulova; S. N. Novikov; A. I. Tseluyko; A. V. Chernaya; Zh. V. Bryantseva; P. V. Krivorotko; S. V. Kanaev (Опухоли женской репродуктивной системы)
Objective: to compare cosmetic result of two techniques of boost delivery to the tumor bed after breast concerving treatment.Materials and methods. A retrospective analysis of the results of treatment of patients with stage IA–IIIA breast cancer from three groups was carried out: 1) 45 women received tumor bed boost with interstitial brachytherapy; 2) 48 women with electrons (energies from 6 to 18 MeV); 3) 59 women did not receive additional irradiation of the removed tumor bed. The analysis of the cosmetic results of treatment was carried out using subjective and objective methods using mammographic data, including information about the most common complications from the skin, subcutaneous fat and remaining breast tissue, such as telangiectasias, fibrosis, and fatty necrosis.Results. According to the results of self-assessment by patients and assessment by independent expert (oncologist), carried out on a 4-point Harvard scale, the cosmetic result in most cases was characterized as “excellent” or “good”. Frequency and grade of telangiectasia were used for objective evaluation of skin complications and were similar in all 3 groups. The incidence of localized fibrosis also did not differ and was most often observed as absent or moderate (grade 1–2). There were no significant differences between the severity and incidence of fatty necrosis on both physical examinations and when it was evaluated on mammography.Conclusions. additional irradiation of the tumor bed does not compromise cosmetic result of the treatment. In most cases (57–78 %) estimated as “good” and “excellent”. The cosmetic result of the treatment does not depend on the technology of boost delivery.